Are the Naica giant crystals deteriorating because of human action?. (December 2020) - Montero-Cabrera, M. E.; Carreño-Márquez, I. J. A.; Castillo-Sandoval, I.; Pérez-Cázares, B.; Fuentes-Cobas, L. E.; Esparza-Ponce, H. E.; Menéndez-Méndez, E.; Fuentes-Montero, M. E.; Castillo-Michel, H.; Eichert, D.; Loredo-Portales, R.; Canche-Tello, J.; et al.
Abstract : The giant gypsum crystals of Naica cave have fascinated scientists since their discovery in 2000. Human activity has changed the microclimate inside the cave, making scientists wonder about the potential environmental impact on the crystals. Over the last 9 years, we have studied approximately 70 samples. This paper reports on the detailed chemical–structural characterization of the impurities present at the surface of these crystals and the experimental simulations of their potential deterioration patterns. Selected samples were studied by petrography, optical and electronic microscopy, and laboratory X-ray diffraction. 2D grazing incidence X-ray diffraction, X-ray μ-fluorescence, and X-ray μ-absorption near-edge structure were used to identify the impurities and their associated phases. These impurities were deposited during the latest stage of the gypsum crystal formation and have afterward evolved with the natural high humidity. The simulations of the behavior of the crystals in microclimatic chambers produced crystal dissolution by 1–4% weight fraction under high CO2 concentration and permanent fog, and gypsum phase dehydration under air and CO2 gaseous environment. Our work suggests that most surface impurities are of natural origin; the most significant anthropogenic damage on the crystals is the extraction of water from the caves.